Pembinaan Kepala Sekolah Terhadap Guru Melalui Emis dalam Pengembangan Pendidikan Keagamaan di Madrasah - Heri Ali Imron; Ahmad Sukandar; N. Hanafiyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Coaching is important in organizations, especially with regard to improving educational services. The purpose of this study was to analyze the form of principal's guidance to teachers through EMIS (Education Management Information System) at MI Banjaran, Bandung Regency. The research method used is case studies. Data were collected from observation, interviews and documentation. The research subject is the Principal of MI Banjaran, Bandung Regency. Meanwhile, the research location in this study is MI Banjaran, Bandung Regency. The results of this study include: 1) The form of guidance for the Principal of MI Banjaran Bandung Regency for teachers is carried out based on two forms, namely general coaching and peer-based coaching. The general guidance in question is the guidance of teachers with a clinical approach, 2) The form of religious education development at MI Banjaran, Bandung Regency, namely the habituation and extracurricular program organized by MI Banjaran, Bandung Regency, including: praying in congregation, reading the Koran before studying, saying greetings when meeting, discipline, Tahfidz Quran, PHBI, and other extracurricular programs. 3) Supporting factors faced by school principals in teacher development through EMIS in developing religious education at MI Banjaran Bandung Regency include: solid principals and teachers, adequacy of human resources who master IT, availability of facilities and IT in madrasas and readiness of students in participating in coaching . The Inhibiting Factors Faced by Principals in Guiding EMIS (Education Management Information System) Teachers in the Development of Religious Education at MI Banjaran Bandung Regency are the lack of parental support and decreased interest and motivation due to mass media/social media.